Examining the effects of urbanization and industrialization on carbon dioxide emission: Evidence from China's provincial regions. (15th April 2017) - Ding, Yang; Li, Feng
Abstract: With rapid economic development and expansion of built environment since the year 2000, urbanization has led to great challenge of reduction targets in energy intensity and carbon dioxide emissions. This paper aims to explore the disaggregate driving force of different sectors and investigate the potential of carbon dioxide reduction of them in the context of rapid urbanization. By using the panel datasets at a provincial level in a LMDI (Logarithmic Mean Divisia Index) model, we investigated the effects of various energy-related and socioeconomic factors on regional carbon dioxide emissions in 30 China's provinces from 2000 to 2013. The results show that the factors of economic development are the largest drivers of regional carbon dioxide emissions, compared with the factors of structural change, energy intensity, and social transition. Meanwhile, evidence is found that the urbanization process has contributed to the regional CO2 emissions in China's provinces through a variety of approaches, including changing the energy use characteristics of urban households, transportation, and business sectors. Finally, we found that the changing trend of these influence factors' effect on regional CO2 emissions varied across different provinces, which means there are significant regional heterogeneity in the influence mechanisms of urbanization process on regional CO2 emissions. Highlights: An extended LMDI (Logarithmic Mean Divisia Index) model is proposed and applied. Transportation's contribution to CO2 emissions increased rapidly in Chinese regions. Urbanization affects CO2 emissions by enhancing urban household energy intensity. The eastern provinces should consider developing knowledge-intensive industries. The western provinces should underline the exploitation of clean energy.